2020
DOI: 10.1186/s13071-020-04442-2
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly and analysis of the transcriptome of the Dermacentor marginatus genes differentially expressed after blood-feeding and long-term starvation

Abstract: Background The ixodid tick Dermacentor marginatus is a vector of many pathogens wide spread in Eurasia. Studies of gene sequence on many tick species have greatly increased the information on tick protective antigen which might have the potential to function as effective vaccine candidates or drug targets for eco-friendly acaricide development. In the current study, RNA-seq was applied to identify D. marginatus sequences and analyze differentially expressed unigenes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 108 publications
2
10
0
Order By: Relevance
“…Although the expression of these proteins found in this study has not been clearly reported in the other research about long-term starving ticks, the mRNA expression of some genes (such as 6-phosphofructo-2-kinase/fructose 2,6-bisphosphatase) related to carbohydrate metabolism in the long-term starved tick Dermacentor marginatus was significantly increased. Most of these proteins were also involved in glycolysis and other cycle reactions related to energy production, but unfortunately, the tissue-specific expression was not clearly given, so it is impossible to accurately compare them with the significantly up-regulated proteins found in this study [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the expression of these proteins found in this study has not been clearly reported in the other research about long-term starving ticks, the mRNA expression of some genes (such as 6-phosphofructo-2-kinase/fructose 2,6-bisphosphatase) related to carbohydrate metabolism in the long-term starved tick Dermacentor marginatus was significantly increased. Most of these proteins were also involved in glycolysis and other cycle reactions related to energy production, but unfortunately, the tissue-specific expression was not clearly given, so it is impossible to accurately compare them with the significantly up-regulated proteins found in this study [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of the long-term starved tick D . marginatus , the transcription levels of mRNAs of proteins associated with metabolism and lipid metabolism plus the mRNAs of carbohydrate metabolism related proteins, were also up-regulated [ 26 ]. Hence, this elevated oxidative phosphorylation activity during prolonged starvation enhances substrate oxidation with the corresponding ATP supply and this could be responsible for the ability of most ticks to survive more than a year without blood acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations